A configuração dos cursos de graduação em Enfermagem no estado de Mato Grosso : expansão e diversificação - Jezus, Sonia Vivian de (2013)
This thesis is inserted in the studies about the policies of higher education, concentrating the discussion on the expansion of undergraduate courses in Nursing, as from the promulgation of Law of Directives and Bases of Education - LDB in 1996.It was found that the undergraduate presential Nursing in Brazil presented indicators of growth higher than other undergraduate courses in the area of health and wellness, suppose, then, that this expansion beyond being reflective of educational policies may also be supported by the implementation of SUS, in 1990 and, more specifically, the program of family health strategy, in 2003, which specifies the need for Nurses in its multidisciplinary team. Faced this, the objective of this study was to analyze the expansion of undergraduate courses in Nursing in the state of Mato Grosso, front of educational and health policies in the period from 1996 to 2011.It was utilized to study the method of quantitative and descriptive, exploratory and explicative, availing himself consolidated data from the Census of Higher Education, available by the Ministry of Education through the National Institute for Educational Research Anísio Teixeira (MEC / INEP), highlighting still the indicators of number of courses, jobs, income, administrative categorie and academic organization. Besides data analysis, was performed document analysis of educational and health policies implemented; history about the history of creation of schools of nursing in Brazil, Midwest region and the State of Mato Grosso and the discussions held by SENADEn in the period studied. The analyzes indicate that the growth rates of the indicators for the nursing program in the state of Mato Grosso follow the national tendency, that in 2011 presented a profile offering undergraduate predominantly by the private non-university. The state registered between 1996 and 2002, growth rate of 100%, offering three university courses in 2002, two in the public institution and one in private institution. In the period 2002 to 2010 we check a change in this configuration, in that the growth rate of 200%, represented an increase of thirteen new courses by the private sector, while in the pubic sector these values were four new courses. In 2011, in Mato Grosso were offered 21 undergraduate courses in nursing, being six public university and fifteen private, and of these one university and fourteen non-university; in relation to vacancies offered, 81.87% were from the private sector, 71.7% were filled, already in the public sector despite a smaller offer had a higher fill rate, totaling 80.9% of the total vacancies filled. Enrollment follow the same trend, with a predominance of the private sector (70.7%) and non- university institutions (61%).We can also infer that the expansion of undergraduate nursing in the state had also influence health policies, the extent that in 2000 there were 97 family health teams, already in 2005 these values corresponded to 586 teams, with coverage of 67% of the population of Mato Grosso, thus expanding the market for this professional work.